ABOUT ALGORITHMIZATION OF CALCULATIONS OF THE ARC STEEL MAKING FURNACE SLAG CONTENT - A. A. Chichko; V. F. Sobolev; N. V. Andrianov; V. V. Pivtsaev; S. V. Terletskij (Литьë и металлургия)
The description of the slag model allowing to optimize the process of steel melting in arc steel-furnace is presented. The functional possibilities of dynamic model of slag on changing of the slag composition, phosphorus extraction, magnesium oxide dissolubility, are shown at the example of model calculations.